METODE KOMPUTASIONAL DINAMIKA FLUIDA DALAM UPAYA OPTIMASI DAN KONTROL KONDISI KERJA DESAIN AIR BLAST FREEZING YANG DIGUNAKAN UNTUK MEMPERTAHANKAN KUALITAS UDANG DI INDONESIA : REVIEW - Tikkos Sihombing; Awaludin Martin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Indonesia, a large country with 17,504 islands and a coastline of 95,161 km, is a country that has natural wealth, especially abundant marine products. The potential of shrimp in Indonesia is included in one of the 10 main commodities that contribute value to the country’s foreign exchange which is an export material with good economic growth and statistics. Air blast freezing is a tool that can be used to maintain the quality of materials by cooling. Computational fluid dynamics is an effective method today and has been widely used in research design, both development and industrial scale, to assist in solving modeling, visualization or control problems to obtain optimal results by reducing the potential for repeated failures in experiments. Therefore, the use of air blast freezing technology is one way to increase Indonesia’s export capacity. By using computational fluid dynamics methods, the control conditions of air blast freezing can be simulated so that the working performance of the tool in maintaining the quality of shrimp exports will be well maintained.